2018
DOI: 10.1016/j.bbamem.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intestinal ascorbic acid uptake by lipopolysaccharide is mediated via transcriptional mechanisms

Abstract: Ascorbic acid (AA) accumulation in intestinal epithelial cells is an active transport process mainly mediated by two sodium-dependent vitamin C transporters (SVCT-1 and SVCT-2). To date, little is known about the effect of gut microbiota generated lipopolysaccharide (LPS) on intestinal absorption of water-soluble vitamins. Therefore, the objective of this study was to investigate the effects of bacterially-derived LPS on AA homeostasis in enterocytes using Caco-2 cells, mouse intestine and intestinal enteroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 73 publications
0
66
0
Order By: Relevance
“…Thus, EtOH exposure can possibly enhance lipid synthesis via acetaldehyde and then acetate, and concomitant lipid accumulation possibly results from a deficit of vitamins, such as thiamine (vitamin B 1 ), riboflavin (vitamin B 2 ), and pantothenic acid (vitamin B 5 ). Vitamin deficiencies are commonly found in patients with AUD (Chen and Schnabl, ; Said, ), and chronic EtOH consumption inhibits carrier‐mediated intestinal vitamin uptake, possibly through IM‐produced LPS (Lakhan and Said, ; Subramanian et al., ). These findings suggest that pathological changes associated with chronic EtOH consumption (e.g., inflammation and liver pathology) may be, in part, a consequence of changes in the IM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, EtOH exposure can possibly enhance lipid synthesis via acetaldehyde and then acetate, and concomitant lipid accumulation possibly results from a deficit of vitamins, such as thiamine (vitamin B 1 ), riboflavin (vitamin B 2 ), and pantothenic acid (vitamin B 5 ). Vitamin deficiencies are commonly found in patients with AUD (Chen and Schnabl, ; Said, ), and chronic EtOH consumption inhibits carrier‐mediated intestinal vitamin uptake, possibly through IM‐produced LPS (Lakhan and Said, ; Subramanian et al., ). These findings suggest that pathological changes associated with chronic EtOH consumption (e.g., inflammation and liver pathology) may be, in part, a consequence of changes in the IM.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo 14 C-AA uptake analysis. For in vitro studies, the post-confluent monolayers of Caco-2 cells were treated with either 20 ng/ml of TNF-␣ or TNF-␣ plus 100 nM celastrol (40) to perform 14 C-AA uptake (44,46). After 48 h, cells were incubated for 30 min in Krebs-Ringer (K-R) buffer at 37°C in the presence of 32 M 14 C-AA and prepared to determine the radioactivity content as described before (44,46).…”
Section: Culturing Of Caco-2 Cellsmentioning
confidence: 99%
“…For in vitro studies, the post-confluent monolayers of Caco-2 cells were treated with either 20 ng/ml of TNF-␣ or TNF-␣ plus 100 nM celastrol (40) to perform 14 C-AA uptake (44,46). After 48 h, cells were incubated for 30 min in Krebs-Ringer (K-R) buffer at 37°C in the presence of 32 M 14 C-AA and prepared to determine the radioactivity content as described before (44,46). For in vivo studies, we used the adult Gulo knockout (KO) mice, which cannot synthesize vitamin C endogenously like humans because of a lack of L-gulono-␥-lactone oxidase (Gulo), an enzyme involved in the terminal step of L-ascorbic acid biosynthesis, and 33 mg of AA was provided in 100 ml of drinking water to meet the mice body requirement.…”
Section: Culturing Of Caco-2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters governing absorption typically lie in the chemical properties of the drug itself and how the host may actively import, or export, the molecule. Early microbiome studies hinted that drug transport may be influenced by the microbiome in a composition dependent manner (Hooper et al, 2001), and multiple animal studies have demonstrated that the microbiome modulates drug absorption (J-K Kim et al, 2018;Subramanian et al, 2018). In this section we will highlight methods for examining the influence of microbes on drug transport.…”
Section: Alternative Alterations To Absorptionmentioning
confidence: 99%